ANALISIS HUBUNGAN BELANJA PEMERINTAH FUNGSI PARIWISATA TERHADAP PRODUK DOMESTIK BRUTO REGIONAL (PDRB) - Dahiri; Marihot Nasution (Pusat Kajian Anggaran, 2017)
Tourism is an industry sector that is being favored in Indonesia to increase economic growth. Nevertheless, the spending on tourism is allocated less than other spendings because of the limited fiscal space of the government. This study examines the relationship between the allocation of government spending on tourism and regional economic growth as measured by Gross Regional Domestic Product (GRDP/PDRB). The tests were conducted with data from 2010 to 2015 for all districts/cities in Indonesia. This is done to see the magnitude of the impact of government spending, especially on tourism, on economic growth.